Do Beliefs and Ease of Use Influence The Intention to Use Digital Wallets? A Test Using Social Factors as Moderating Variable - Kumalasari, Siska; Diptyana, Pepie (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
This research aims to examine whether beliefs and ease of use influence the intention to use digital wallets using social factors as moderating variables. Data was gathered by questionnaires collected from 105 respondents. All respondents were19-23 years old, and they were university students at Surabaya. The hypotheses were tested using WarpPLS 8.0. The hypotheses test results show that beliefs as a significant factor that influences the intention to use the digital wallet. Furthermore, social factors are also significant as moderating variables to relationship beliefs and intention to use. However, perceived ease of use is not supported to influence intention to use and social factors do not moderate the relationship between perceived ease of use and intention to use.